2012
DOI: 10.1007/s00595-012-0250-5
|View full text |Cite
|
Sign up to set email alerts
|

Prompt or delayed appendectomy? Influence of timing of surgery for acute appendicitis

Abstract: Performing appendectomy within 24 h from presentation does not increase the length of hospital stay or rate of complications. However, delayed appendectomy after 24 h from onset increases the rate of complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
53
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 19 publications
4
53
1
Order By: Relevance
“…[20][21][22][23][24][25][49][50][51][52][53] The results of our study demonstrate that appendectomy is infrequently performed after hours in Canadian tertiary hospitals, although variation across sites does exist. This practice variation could be explained by site-specific surgical policies or established management pathways, resource availability, or the use of ED observation units.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…[20][21][22][23][24][25][49][50][51][52][53] The results of our study demonstrate that appendectomy is infrequently performed after hours in Canadian tertiary hospitals, although variation across sites does exist. This practice variation could be explained by site-specific surgical policies or established management pathways, resource availability, or the use of ED observation units.…”
Section: Discussionmentioning
confidence: 78%
“…Traditionally, appendicitis has been considered a surgical emergency in an attempt to mitigate adverse patient outcomes (perforation, abscess formation, sepsis). Recent literature, however, demonstrates that delaying appendectomy until daytime hours may be safe practice and has fueled the debate between emergent and urgent appendectomy, [20][21][22][23][24][25][26] nonsurgical management of uncomplicated appendicitis, [27][28][29] and the potential effect these approaches may have on patient outcomes such as perforation. Antibiotic monotherapy in uncomplicated appendicitis has been proposed as an alternative to traditional triple therapy to simplify ED processes, reduce error, and decrease antibiotic resistance.…”
mentioning
confidence: 99%
“…Among these three features, the CRP level was the only preoperative risk factor for SSI in patients with appendicitis. Although gangrenous or perforated appendicitis and delayed diagnosis have already been reported as risk factors for postoperative complications in patients undergoing appendectomy [20,21], few reports have demonstrated that the preoperative CRP level (>65 mg/l) is a risk factor for SSI in such patients. CRP is synthesized in the liver in response to interleukin-6 (IL-6) and is commonly used as a non-specific inflammatory marker in patients with an acute abdomen in many clinical settings [22].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that there is a correlation between the time since the onset of symptoms and the risk factor for an event of complicated appendicitis [14]. However, that does not impact patients who are hospitalised and treated with intravenous hydration and antibiotics [15,16]. In developed countries 15% to 30% of appendicitis cases are complicated [17,18].…”
Section: Discussionmentioning
confidence: 99%